Pengaruh Rating dan Kupon Terhadap Harga Obligasi : Studi Kasus Obligasi Kriterian Investasi Yang Terdaftar Di Bursa Efek Surabaya Tahun 2002-2006 - Achmad, Noor; Setiawan, Greace (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
The price of bonds are the most important indicator to determine an investment by a prospective investor, because price is discounted everything related to itâs atributes like rating, coupon maturity, etc. The price of bonds are important matter in the purchase of bonds to examine whether these bonds are priced approprite by to be chosen by investor in investing his fund for long term period. Moreover, the price of the bonds is useful tools to facilitate the asesment of financial conditions the publisher. To measure corelation in analysing rating, coupon and the price of the bonds by using statistical method chi square and the variance to be analysed by using the F-Test. The aim of this research is to measure the influence of rating and coupon against price of the bonds which were listed in the Surabaya Stock Exchange. The analysis carried out to measure the relations between bonds rating and coupon against the price of the bonds either individually or simultaneously. The reseach is done through fifty four (54) investment criteria bonds which are issued by twenty nine (29) companies and listed in the Surabaya Stock Exchange during period 2002-2006. The results of the analysis in this study found out that there are significant corelation between rating of the bonds against the price of the bonds. But coupon of the bonds against the price of the bonds do not have significant relations due to inflation factor was much more significant determinant that discounted the bondâs price. Meanwhile bondâs rating and coupon simultaneously has significant relations the price of the bonds eventhogh in a low level. This finding mean that the bondâs price is not discounted said determinants only but inflation factor as well. Keywords : Rating, coupon, inflation rate, and bondâs price.